Business, the state and economic policy : the case of Italy - Amyot, Grant (Routledge advances in European politics, 2004)
"Grant Amyot casts his critical eye upon the Italian business world, setting it in the context of the international economy. He then traces the close, but chequered, relationship between capital, the state, and the political parties up to the election of one of the country's major business magnates, Silvio Berlusconi, as Prime Minister. The book compares Italy with the USA, Germany and Japan and explores the influence of economic realities, organized interests, and political institutions on the formation of policy in Italy." "This interesting, readable and important book gives the reader an insight into the sources and workings of power in a major advanced industrial state. It will be appreciated by students and researchers with an interest in European politics, comparative politics, and political economy. It will also be a good tool for policy-makers and professionals with an interest in Italian business, economics and politics."--BOOK JACKET.